KEANEKARAGAMAN LALAT BUAH Bactrocera sp DI SCIENCE TECHNO PARK UNIVERSITAS TRIBHUWANA TUNGGADEWI - Krismarianto, Gerson; Agastya, I Made Indra; Wakhid, Wakhid (BUANA SAINS, 2024)
The one pest that can potentially cause harm to fruit cultivation is fruit flies (Bactrocera spp). The fruit flies cause losses in qualitative and quantitative terms in Indonesia and are classified as Bactrocera. It is necessary to identify the diversity of fruit flies in Science Techno Park ( STP) University of Tribhuwana Tunggadewi and handle them. This research aimed to determine the types of fruit flies and how to handle them. The method used in this research is a systematic sampling method, by taking 1 sample at each point of the bottle trap is given an attractant. The results showed that there are found three species of fruit flies at the STP location. The three species of fruit flies found in the STP are Bactrocera dorsalis, Bactrocera carambola, and Bactrocera umbrosa. B. dorsalis has the highest abundance with 82.7%, followed by B. carambola at 16.3%, and the lowest is B. umbrosa at 0.8%. The highest dominance of the fruit fly species in the STP was B. dorsalis value D 0.82.